2019
DOI: 10.1038/s41593-019-0393-4
|View full text |Cite
|
Sign up to set email alerts
|

A single-cell atlas of mouse brain macrophages reveals unique transcriptional identities shaped by ontogeny and tissue environment

Abstract: Increasing evidence suggests that macrophages critically shape brain homeostasis and disease.However, while the pivotal role of parenchymal microglia has gradually emerged, other brain-resident myeloid cells remain elusive. By dissecting border regions and combining single-cell RNA sequencing with high-dimensional cytometry, bulk RNA-sequencing, fate-mapping and microscopy, we reveal the remarkable diversity of non-parenchymal brain macrophages. Border-associated macrophages or BAMs residing in the dura mater,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

58
819
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 685 publications
(963 citation statements)
references
References 79 publications
58
819
1
1
Order By: Relevance
“…In the choroid plexus, P2ry12-CreER recombination marked a small number of IBA1 + cells, as well as a small number of IBA1-negative or IBA1-low cells, unlike Cx3cr1-CreER, which showed recombination in most choroid plexus IBA1 + macrophages ( Figure 1G). Some of the P2ry12-CreER; Ai14 recombined cells appeared to be on the surface of the choroid plexus, consistent with a recently published study that revealed a microglia-like, P2ry12-expressing "CP-epi" subpopulation of choroid plexus macrophages, which may be Kolmer's epiplexus cells (Ling et al, 1998;Van Hove et al, 2019).…”
Section: P2ry12-creer-mediated Recombination Efficiently and Specificsupporting
confidence: 89%
“…In the choroid plexus, P2ry12-CreER recombination marked a small number of IBA1 + cells, as well as a small number of IBA1-negative or IBA1-low cells, unlike Cx3cr1-CreER, which showed recombination in most choroid plexus IBA1 + macrophages ( Figure 1G). Some of the P2ry12-CreER; Ai14 recombined cells appeared to be on the surface of the choroid plexus, consistent with a recently published study that revealed a microglia-like, P2ry12-expressing "CP-epi" subpopulation of choroid plexus macrophages, which may be Kolmer's epiplexus cells (Ling et al, 1998;Van Hove et al, 2019).…”
Section: P2ry12-creer-mediated Recombination Efficiently and Specificsupporting
confidence: 89%
“…2B). Furthermore, monocytes are short‐lived cells, while all the macrophage populations at least partially self‐renew from an internal pool . We did not observe tamoxifen‐independent Zsgreen expression in blood monocytes from Cx3cr1 CreERT2 :R26‐CAG‐Zsgreen mice (Fig.…”
mentioning
confidence: 72%
“…Five independent, publicly available, murine RNA‐sequencing datasets were used to compare with our human datasets (Bowman et al, ; Heng et al, ; Pluvinage et al, ; Qian et al, ; Van Hove et al, ). Differential gene expression analysis was completed with edgeR package (Robinson, McCarthy, & Smyth, ).…”
Section: Methodsmentioning
confidence: 99%